Mental Models for the Negation of Conjunctions and Disjunctions - Macbeth, Guillermo Eduardo (2014)
This study investigates why reasoning that involves negation is extremely difficult. We presented participants with reasoning problems containing sentences with negation of conjunctions and disjunctions in order to test predictions derived from the Mental Models Theory of human thought. According to this theory, reasoning consists of representing and comparing possibilities. Different sentential forms would require different cognitive demands. In particular, responses to a sentential negation task would be modulated by working memory load. This prediction would hold for correct responses but also for the general pattern of responses that includes incorrect responses when the task offers different response options. A within-subjects experimental design with selection paradigm was applied to test these predictions. Experimental comparisons and a complementary descriptive study yielded evidence consistent with the theory-driven predictions derived from the Mental Models Theory. The working memory load was critical for the modulation of correct responses and overall responses. We discussed alternative accounts, and suggested additional predictions for further evaluation of these phenomena.